Extraordinary deformation capacity of smallest carbohelicene springs - Šesták, Petr; Wu, Jianyang; He, Jianying; Pokluda, Jaroslav; Zhang, Zhiliang (Physical chemistry chemical physics, 2015)
The extraordinary deformation and loading capacity of nine different [∞]carbohelicene springs under uniaxial tension up to their fracture were computed using the density functional theory. The simulations comprised either the experimentally synthetized springs of hexagonal rings or the hypothetical ones that contained irregularities (defects) as, for example, pentagons replacing the hexagons. The results revealed that the presence of such defects can significantly improve mechanical properties. The maximum reversible strain varied from 78% to 222%, the maximum tensile force varied in the range of 5 nN to 7 nN and, moreover, the replacement of hexagonal rings by pentagons or heptagons significantly changed the location of double bonds in the helicenes. The fracture analysis revealed two different fracture mechanisms that could be related to the configurations of double and single bonds located at the internal atomic chain. Simulations performed with and without van der Waals interactions between intramolecular atoms showed that these interactions played an important role only in the first deformation stage.